A Clinical Practice Guideline for the Management of Patients With Acute Spinal Cord Injury: Recommendations on the Type and Timing of Rehabilitation - Fehlings, Michael G. (Global Spine J, 2017)
INTRODUCTION: The objective of this study is to develop guidelines that outline the appropriate type and timing of rehabilitation in patients with acute spinal cord injury (SCI). METHODS: A systematic review of the literature was conducted to address key questions related to rehabilitation in patients with acute SCI. A multidisciplinary guideline development group used this information, and their clinical expertise, to develop recommendations for the type and timing of rehabilitation. Based on GRADE (Grading of Recommendation, Assessment, Development and Evaluation), a strong recommendation is worded as “we recommend,” whereas a weaker recommendation is indicated by “we suggest. RESULTS: Based on the findings from the systematic review, our recommendations were: (1) We suggest rehabilitation be offered to patients with acute spinal cord injury when they are medically stable and can tolerate required rehabilitation intensity (no included studies; expert opinion); (2) We suggest body weight–supported treadmill training as an option for ambulation training in addition to conventional overground walking, dependent on resource availability, context, and local expertise (low evidence); (3) We suggest that individuals with acute and subacute cervical SCI be offered functional electrical stimulation as an option to improve hand and upper extremity function (low evidence); and (4) Based on the absence of any clear benefit, we suggest not offering additional training in unsupported sitting beyond what is currently incorporated in standard rehabilitation (low evidence). CONCLUSIONS: These guidelines should be implemented into clinical practice to improve outcomes and reduce morbidity in patients with SCI by promoting standardization of care, decreasing the heterogeneity of management strategies and encouraging clinicians to make evidence-informed decisions.